A NEW METHOD FOR THE PREDICTION OF GIBBS FREE ENERGIES OF FORMATION OF PHYLLOSILICATES (10 Å AND 14 Å) BASED ON THE ELECTRONEGATIVITY SCALE - Vieillard P. (My University, 2002)
The method for prediction of Gibbs free energies of formation, based on the parameter Δ G O=M z+(clay) characterizing the oxygen affinity of the cation M z+, on the smectites, considered as hydrated clay minerals, has been used for micas and brittle micas, and yielded underestimated values. This method of prediction can be improved by a new set of parameters Δ GO=M z+(clay), characterizing the electronegativity of a cation in a specific site (interlayer, octahedral, tetrahedral in the 10 Å minerals), determined by minimizing the difference between experimental Gibbs free energies and calculated Gibbs free energies of formation from constituent oxides. By considering the crystal structure of 10 Å and 14 Å minerals, and assuming the same electronegativity of cations, Δ G O=M z+(o), in the octahedral sheets, an attempt is made to determine the electronegativity of cations in the brucitic sheet, Δ G O=M z+(b). The results indicate that this prediction method compared to other determinations, gives values within 0.25% of the experimentally-estimated values. The relationships between Δ G O=M z+(clay) corresponding to the electronegativity of a cation in the interlayer, octahedral, tetrahedral or brucitic sites and known Δ G O=M z+(aq) were thus determined, allowing the determination of the electronegativity of transition metal ions and trivalent ions in each of the four sites and consequently contribute to the prediction of Gibbs free energies of formation of different micas and chlorites. Examples are given for low-Fe clinochlore whose solubility is measured experimentally and the results appear excellent when compared with experimental values.